A Comparison Study of the Blood Component Quality of Whole Blood Held Overnight at 4°C or Room Temperature. (5th September 2013) - Wang, Shichun; Wang, Tiantian; Fan, Yahan; Huang, Shan; Yi, Zhongmei; Li, Ruiqing; Zhao, Shuming
Abstract : Background . The use of plasma frozen within 24 hrs is likely to increase. Whole blood (WB) and buffy coats (BCs) can be held for a few hrs or overnight before processing. Methods . Twenty-four bags of WB for plasma and 12 bags for platelet (PLT) concentrates were collected. The fresh frozen plasma (FFP) was prepared within 6 hrs. I-FP24 and II-FP24 samples were prepared either from leukodepleted WB that was held overnight or from WB that was held overnight before leukodepletion. The PLT concentrates (PCs) were prepared from BCs within 6 hrs (PC1) and within 18 to 24 hrs (PC2). The typical coagulation factors and some biochemical parameters were determined. Results . Compared to the FFP samples, the levels of FVII and FVIII in the I-FP24 and II-FP24 samples decreased significantly. The pH, Na +, LDH, and FHb levels differed significantly between II-FP24 and FFP. Compared to PC1, PC2 exhibited lower pH, pO2, and Na + levels, a higher PLT count, and increased pCO2, K +, Lac, and CD62P expression levels. Conclusion . FP24 is best prepared from WB that was stored overnight at 4°C and then leukodepleted and separated within 24 hrs. PCs are best produced from BCs derived from WB that was held overnight at room temperature.